The early response of oil palm (Elaeis guineensis Jacq.) plants to water deprivation: Expression analysis of miRNAs and their putative target genes, and similarities with the response to salinity stress - Salgado, Fernanda Ferreira; da Silva, Thalliton Luiz Carvalho; Vieira, Letícia Rios; Silva, Vivianny Nayse Belo; Leão, André Pereira; Costa, Marcos Mota do Carmo; Togawa, Roberto Coiti; de Sousa, Carlos Antônio Ferreira; Grynberg, Priscila; Souza, Manoel Teixeira (Frontiers in Plant Science, 2022)
Oil palm (Elaeis guineensis Jacq.) is a oilseed crop of great economic importance drastically affected by abiotic stresses. MicroRNAs (miRNAs) play crucial roles in transcription and post-transcription regulation of gene expression, being essential molecules in the response of plants to abiotic stress. To better understand the molecular mechanisms behind the response of young oil palm plants to drought stress, this study reports on the prediction and characterization of miRNAs and their putative target genes in the apical leaf of plants subjected to 14 days of water deprivation. Then, the data from this study was compared to the data from a similar study that focused on salinity stress. Both, the drought- and salt-responsive miRNAs and their putative target genes underwent correlation analysis to identify similarities and dissimilarities among them. Among the 81 identified miRNAs, 29 are specific for oil palm, including two (egu-miR28ds and egu-miR29ds) new ones - described for the first time. As for the expression profile, 62 miRNAs were significantly differentially expressed under drought stress, being five up-regulated (miR396e, miR159b, miR529b, egu-miR19sds, and egu-miR29ds) and 57 down-regulated. Transcription factors, such as MYBs, HOXs, and NF-Ys, were predicted as putative miRNA-target genes in oil palm under water deprivation; making them the most predominant group of such genes. Finally, the correlation analysis study revealed a group of putative target genes with similar behavior under salt and drought stresses. Those genes that are upregulated by these two abiotic stresses encode lncRNAs and proteins linked to stress tolerance, stress memory, modulation of ROS signaling, and defense response regulation to abiotic and biotic stresses. In summary, this study provides molecular evidence for the possible involvement of miRNAs in the drought stress response in oil palm. Besides, it shows that, at the molecular level, there are many similarities in the response of young oil palm plants to these two abiotic stresses.